2016
DOI: 10.3758/s13421-016-0613-z
|View full text |Cite
|
Sign up to set email alerts
|

All my children: The roles of semantic category and phonetic similarity in the misnaming of familiar individuals

Abstract: Despite knowing a familiar individual (such as a daughter) well, anecdotal evidence suggests that naming errors can occur among very familiar individuals. Here, we investigate the conditions surrounding these types of errors, or misnamings, in which a person (the misnamer) incorrectly calls a familiar individual (the misnamed) by someone else's name (the named). Across 5 studies including over 1,700 participants, we investigated the prevalence of the phenomenon of misnaming, identified factors underlying why i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…These results concerning the impact of phonological and semantic similarity on name confusions are consistent with the previous retrospective studies investigating name confusions (Brédart & Dardenne, 2015; Deffler et al., 2016; Fiske et al., 1991; Fraas et al., 2002), which also showed that name confusions were influenced by both semantic and phonological similarities. An explanation of why semantically or phonologically related names tend to be more frequently confounded than unrelated ones can be found in the interactive models of word production (see Damian & Martin, 1999; Levelt, 1993; Levelt, 1999; Dell, Schwartz, Martin, Saffran, & Gagnon, 1996; Starreveld & La Heij, 1995, 1996; Stemberger, 1985).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results concerning the impact of phonological and semantic similarity on name confusions are consistent with the previous retrospective studies investigating name confusions (Brédart & Dardenne, 2015; Deffler et al., 2016; Fiske et al., 1991; Fraas et al., 2002), which also showed that name confusions were influenced by both semantic and phonological similarities. An explanation of why semantically or phonologically related names tend to be more frequently confounded than unrelated ones can be found in the interactive models of word production (see Damian & Martin, 1999; Levelt, 1993; Levelt, 1999; Dell, Schwartz, Martin, Saffran, & Gagnon, 1996; Starreveld & La Heij, 1995, 1996; Stemberger, 1985).…”
Section: Discussionsupporting
confidence: 92%
“…Other similarities between the target and the intruder increased these substitutions, such as gender, age, and other semantic information (having the same occupation, for example). More recently, Griffin and Wangerman (2013) and Deffler, Fox, Ogle, and Rubin (2016) analyzed naturally occurring substitutions made by parents with their children (calling a child by the name of one of his or her brothers or sisters). The authors found that phonological similarity between the siblings’ names increased the occurrence of name substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…In a study led by the team of Samantha Deffler (2016), it was demonstrated how in the human memory the dogs of the home are cataloged as family members. There are few lapsus linguae where one of the members of the family is called by the name of the dog.…”
Section: The Deep Bondmentioning
confidence: 99%
“…Generally, the answer is yes: Semantically related names of people who also share visual features, including similarity in facial features and other measures of physical appearance, are sometimes associated with more person-misnaming errors—that is, use of the wrong name to refer to a familiar person (Brédart & Dardenne, 2015; Griffin & Wangerman, 2013; but see Deffler, Fox, Ogle, & Rubin, 2016). Another type of overlap that increases misnaming errors is phonological (shared sounds); the names produced through misnaming errors are more likely to possess both semantic and phonological properties of the intended name (Brédart & Dardenne, 2015; Brédart & Valentine, 1992; Deffler et al, 2016). For example, phonological similarity, in the form of shared initial or final sounds between the names of siblings (whose names by definition share semantic attributes), increased the frequency with which parents used a sibling’s name instead of the intended name (Griffin & Wangerman, 2013).…”
Section: Related Names Can Hurt or Help Retrievalmentioning
confidence: 99%